2023
DOI: 10.1111/gcb.16851
|View full text |Cite
|
Sign up to set email alerts
|

Individual and interactive effects of warming and nitrogen supply on CO2 fluxes and carbon allocation in subarctic grassland

Abstract: Climate warming has been suggested to impact high latitude grasslands severely, potentially causing considerable carbon (C) losses from soil. Warming can also stimulate nitrogen (N) turnover, but it is largely unclear whether and how altered N availability impacts belowground C dynamics. Even less is known about the individual and interactive effects of warming and N availability on the fate of recently photosynthesized C in soil. On a 10‐year geothermal warming gradient in Iceland, we studied the effects of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 127 publications
0
1
0
Order By: Relevance
“…However, Callebaut (2022) showed that leaf‐level photosynthetic capacity in one of the dominant vascular plant species was reduced in warmed plots, due primarily to reduced foliar N concentrations. Nitrogen has indeed been identified to limit grassland productivity in Iceland (Leblans et al ., 2014, 2017a,b; Meeran et al ., 2023), and this limitation has been aggravated in many other northern areas with low atmospheric N deposition (Liu et al ., 2020). The strong decline in soil N–P ratio at our study site indeed suggests that N limitation in these grasslands aggravated in response to decadal warming (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, Callebaut (2022) showed that leaf‐level photosynthetic capacity in one of the dominant vascular plant species was reduced in warmed plots, due primarily to reduced foliar N concentrations. Nitrogen has indeed been identified to limit grassland productivity in Iceland (Leblans et al ., 2014, 2017a,b; Meeran et al ., 2023), and this limitation has been aggravated in many other northern areas with low atmospheric N deposition (Liu et al ., 2020). The strong decline in soil N–P ratio at our study site indeed suggests that N limitation in these grasslands aggravated in response to decadal warming (Fig.…”
Section: Discussionmentioning
confidence: 99%